Catenary action effects on the structural robustness assessment of RC slab strips subjected to shear and tensile forces. (December 2016) - Belletti, Beatrice; Damoni, Cecilia; Cervenka, Vladimir; Hendriks, Max A.N.
Abstract: In this paper, the behaviour of RC slab strips subjected to transverse loads and axial tensile forces is investigated by means of analytical and numerical simulations. The results obtained are compared to the experimental results from tests performed at the Swiss Federal Institute of Technology (ETH). The prediction of the structural response was part of an international benchmark study [1]. The aim of the paper is to investigate the capability of the adopted models and their main influencing parameters, especially from the perspective of a reliable structural robustness assessment. It is known that in some cases axial tensile forces have a beneficial effect on the bearing capacity of slab strips, thanks to the development of catenary actions. Such hidden strength resources are usually not taken into account in the current design process. For this reason, validation of suitable numerical tools, able to properly predict the structural response, is useful for a reliable structural robustness assessment. The paper underlines the importance of benchmark development, especially for specimens, in which both mechanical and geometrical nonlinearities play an important role.